Nonmonotonous variation of DNA angular separation during asymmetric pulsed field electrophoresis. Issue 17 (26th July 2013) - Nazemifard, Neda; Bhattacharjee, Subir; Masliyah, Jacob H.; Harrison, D. Jed
<x xml:space="preserve">Abstract</x> Asymmetric pulsed field electrophoresis within crystalline arrays is used to generate angular separation of DNA molecules. Four regimes of the frequency response are observed, a low frequency rise in angular separation, a plateau, a subsequent decline, and a second plateau at higher frequencies. It is shown that the frequency response for different sized DNA is governed by the relation between pulse time and the reorientation time of DNA molecules. The decline in angular separation at higher frequencies has not previously been analyzed. Real‐time videos of single DNA molecules migrating under high frequency‐pulsed electric field show the molecules no longer follow the head to tail switching, ratchet mechanism seen at lower frequencies. Once the pulse period is shorter than the reorientation time, the migration mechanism changes significantly. The molecule reptates along the average direction of the two electric fields, which reduces the angular separation. A freely jointed chain model of DNA is developed where the porous structure is represented with a hexagonal array of obstacles. The model qualitatively predicts the variation of DNA angular separation with respect to frequency.